(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The aim of this study was to find out the effect of strength training and aqua therapy in therehabilitation of ACL injury. To achieve the purpose of this study, the investigator selected 60 sportsmenwho were treated for ACL injuries in Andhra Pradesh. Their age between 18 and 28 years. theinvestigator considered for this study as ACL injuries, which occurs in knee due to other majorligaments and dependent variables, flexibility measured through sit and reach and half squat wereselected. The subjects (n=60) were randomly assigned to three equal groups of twenty in each. Thegroups were assigned as Experimental Groups I, II and control group respectively. Pre tests wereconducted for all the subjects on selected criterion variables, flexibility and half squat using standardtests. The experimental groups participated in their respective experimental treatments for four weekswhile control group was not. Immediately after the completion of the experimental period the criterionvariables were measured and the post test scores obtained. The difference between the pre and post testscores on each variable was considered as the effect of respective treatments. To find out the statisticalsignificance, ANCOVA was employed. The results showed that there was significant improvement dueto strength and aqua therapy exercises among the ACL injured. The paired adjusted mean comparisonsbetween the groups proved that strength training and aqua therapy were equally good in improvingflexibility than control group while strength training was found to be significantly better than aquatherapy and control group in improving half squat test. Hence it was concluded that strength trainingstretches and aqua therapy would be significantly contributing to improve ACL injured in the process oftheir rehabilitation.